INOVASI DALAM PENDIDIKAN: OPTIMALISASI PENGGUNAAN PROMPT CHATGPT UNTUK MENDUKUNG PEMBELAJARAN SISWA DI MADRASAH ALIYAH - Mandailina, Vera; Syaharuddin, Syaharuddin; Muhamad, Muhamad; Arif, April Mulyanas; Saputra, Andi; Ratnasari, Desi; Aryani, Nofi; Hadawiyah, Roqib Atul; Hartoyo, Servasius (LPPM Universitas Bina Bangsa, 2025)
ChatGPT has emerged as a crucial tool in educational settings, necessitating students to develop proficiency in its use. This program aimed to enhance the knowledge and skills of MA students in utilizing ChatGPT prompts as an essential educational medium. A total of 30 students participated in the training, during which they were introduced to various AI tools, including ChatGPT, Gemini, and Perplexity. The training methodology combined theoretical instruction with practical sessions focused on the application of ChatGPT prompts to support learning processes. The effectiveness of the program was evaluated using questionnaires and observations. The results indicated a positive response from participants, with an average score of 86.4. Despite challenges such as limited time and weak internet connectivity, these issues were effectively managed and resolved promptly. Consequently, the optimization of ChatGPT prompts for enhancing learning in Madrasah Aliyah proved to be both effective and efficient.